Mutasi Terhadap Kinerja Karyawan Pada PT Kereta Api Indonesia (Persero) Daerah Operasi 1 Jakarta - Ferdian Erlangga Rosa (Agregat: Jurnal Ekonomi dan Bisnis, 2017)
This study aims to determine the effect of the mutation on the performance of employees at PT Kereta Api Indonesia (Persero) Regional Operations 1 Jakarta. In this study using survey methods and eksplansi with the collection directly from the original source, in the form of questionnaires were drawn from a sample. The sample in this study were all employees of PT Kereta Api Indonesia (Persero) Jakarta Regional Operations 1 102 respondents. Data analysis and processing techniques used are validity, reliability test, descriptive analysis, simple linear regression analysis. Based on the results of data processing test "t" to see the effect of the mutation on employee performance variables significant or not, it can be seen from the figures the probability (sig). Probability value 0.000 <0.05 by t value = 6.305 and t table = 1.66023. 1.66023 Figures obtained from the t table with α = 0.05 and degrees of freedom (df) nk-1 = 100. If t> t table is 6.305> 1.66023, so it can be concluded that Ho is rejected or mutations significantly influence employee performance